On the Role of Music in First Communion Catechesis: Importance and Implications for Practice - Chrostowski, Mariusz; Siegert, Julia Maria (Studia Teologiczne Białystok Drohiczyn Łomża, 2023)
The problem of this article focuses on the role of music in the catechesis of the First Communion. The analysis begins with the question of the affinity between music and the Christian faith, in order to then present the significance of music and its multiple functions (i.e. mystagogical, community-building, aesthetic, spiritual, preparatory, pedagogical and therapeutic functions) within First Communion catechesis. Finally, some practical implications for the use of music in First Communion catechesis in the parish are presented.